The Davidson Debate : Bourgeois Revolutions in Historical Perspective - Davidson, Neil, (Historical Materialism Book Series ;, 2025)
In the words of Mike Davis, Neil Davidson's How Revolutionary Were the Bourgeois Revolutions? (2012) "resets the entire debate on the character of revolutions: bourgeois, democratic, and socialist". Epic in scale and nuanced in its address to a wide range of questions on the emergence of capitalism, Davidson's book made a major contribution to understanding the historical character of political change. The Davidson Debate brings Bridget Fowler's introduction to the debates, with three important responses to the book by Dylan Riley, Charles Post and Heide Gerstenberger, as well as the authors long and sustained reply to his critics. Supplementing and extending his earlier work, this book represents an important further contribution to Marxist scholarship. The Davidson debate will, no doubt continue, and this collection will play an important role in future discussion of the important questions it addressed.